2007
DOI: 10.1177/1557988307301276
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Putting Condoms On After Sex Has Begun and of Removing Them Before Sex Ends: A Study of Men Attending an Urban Public STD Clinic

Abstract: This study aimed to identify possible correlates of putting condoms on after sex has begun and taking them off before sex has ended among male patients of an urban, public sexually transmitted disease clinic. Participants responded to a questionnaire and were largely African American men, 18 to 35 years old, who had used a condom during penile-vaginal intercourse at least three times in the past 3 months. In controlled analyses, men who were not highly motivated to use condoms correctly were nearly twice as li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
(24 reference statements)
1
25
2
Order By: Relevance
“…Further, the association between perceived pleasure loss and UAI reported by men in the insertive position is consistent with other literature tying condom use to condom fit and feel; condom discomfort by condom wearers has been linked to incomplete condom use during intercourse (e.g., early condom removal), 17,20,28 lower motivation for condom use, 17 and lower likelihood of condom use during anal intercourse. 18 Manufacturing companies' continued improvements in male condom texture, lubrication, and other physical properties as well as their production of condoms that vary by size and shape will help to accommodate diversity in tactile preferences and genital dimensions across male condom wearers.…”
Section: Discussionsupporting
confidence: 88%
“…Further, the association between perceived pleasure loss and UAI reported by men in the insertive position is consistent with other literature tying condom use to condom fit and feel; condom discomfort by condom wearers has been linked to incomplete condom use during intercourse (e.g., early condom removal), 17,20,28 lower motivation for condom use, 17 and lower likelihood of condom use during anal intercourse. 18 Manufacturing companies' continued improvements in male condom texture, lubrication, and other physical properties as well as their production of condoms that vary by size and shape will help to accommodate diversity in tactile preferences and genital dimensions across male condom wearers.…”
Section: Discussionsupporting
confidence: 88%
“…[10][11][12][13][14][15][16] Seven studies reported the prevalence of late application as a proportion of condom use events, with estimates ranging from 1.5% to 24.8%. [16][17][18][19][20][21][22] Six studies reported early removal at the participant level, with prevalence ranging from 13.6% to 44.7%. 11,[13][14][15]19,23 Six studies reported early removal at the event level, with prevalence ranging from 1.4% to 26.9%.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Six studies reported early removal at the participant level, with prevalence ranging from 13.6% to 44.7%. 11,[13][14][15]19,23 Six studies reported early removal at the event level, with prevalence ranging from 1.4% to 26.9%. [16][17][18][20][21][22] Finally, two studies reported a combined prevalence (either late application or early removal or both), ranging from 20.0% to 60.0% of participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although much of this research has been descriptive, few studies have identified likely causes of these problems. 5,7,8,14 For example, allowing condoms to contact sharp objects, reporting problems with 'fit-and-feel' condoms and having low self-efficacy to use condoms correctly may predispose men to experience condom breakage. 8 Loss of erection and inadequate lubrication have been associated with slippage.…”
Section: Introductionmentioning
confidence: 99%